2021
DOI: 10.1002/ece3.8083
|View full text |Cite
|
Sign up to set email alerts
|

The effects of released pheasants on invertebrate populations in and around woodland release sites

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Previous work has suggested that particular taxa may be especially sensitive to these activities, but the direction and magnitude of the effects is contentious, with empirical studies and hypothesized mechanisms supporting both increases and decreases (reviewed by Madden & Sage, 2020 ; Mason et al, 2020 ; Sage et al, 2020 ). Some specific examples include: avian predators Pringle et al, 2019 ; invertebrates Hall et al, 2021 ; Woodland birds Draycott et al, 2008 ; vegetation Sage et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has suggested that particular taxa may be especially sensitive to these activities, but the direction and magnitude of the effects is contentious, with empirical studies and hypothesized mechanisms supporting both increases and decreases (reviewed by Madden & Sage, 2020 ; Mason et al, 2020 ; Sage et al, 2020 ). Some specific examples include: avian predators Pringle et al, 2019 ; invertebrates Hall et al, 2021 ; Woodland birds Draycott et al, 2008 ; vegetation Sage et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate populations, predominantly insects, have been proposed to increase due to habitat creation and management or nutrient enrichment (e.g. Hall et al, 2021 ; Robertson et al, 1988 ). Conversely, populations at release sites may decline or change in composition due to direct predation if eaten by omnivorous gamebirds or because of habitat damage (e.g., Hall et al, 2021 ; Neumann et al, 2015 ; Pressland, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations